Comparative study of methods for extraction and purification of environmental DNA from high-strength wastewater sludge - Tabatabaei, Meisam; Zakaria @ Mamat, Mohd Rafein; Abdul Rahim, Raha; Abdullah, Norhani; Wright, Aandré-Denis G.; Shirai, Yoshihito; Shamsara, Mehdi; Sakai, Kenji; Hassan, Mohd Ali (Academic Journals, 2010)
DNA extraction from wastewater sludge (COD 50000 and BOD 25000 mg/l) was conducted using nine different methods normally used for environmental samples including a procedure used in this study and the results obtained were compared. The quality of the differently extracted DNAs was subsequently assessed by measuring humic acid concentration, cell lysis efficiency, polymerase chain reaction (PCR) amplification of methanogenic and eubacterial 16S rDNA. The protocol developed in this study was further evaluated by extracting DNA from various high-strength wastewater sludge samples, denaturing gradient gel electrophoresis (DGGE) and fluorescent in situ hybridization (FISH) analyses. The results revealed that great differences existed among the nine procedures and only a few produced satisfactory results when applied to high-strength wastewater sludge. Thermal shock alone was shown inefficient to disrupt the methanogenic cell wall to release the DNA. The method presented in this study (Procedure 9) is generally recommended because of the low concentration of contaminants and its high efficiency despite its simplicity.